Hospital wastewater as hotspots for pathogenic microorganisms spread into aquatic environment: A review - Yuan, Tingting; Pian, Yaya (Frontiers in Environmental Science, 2023)
Combined with human-to-human contact, the potential for SARS-CoV-2 virus transmission via aerosols and feces raises the urgency for effective treatment of hospital wastewater (HWW), which has been assumed as an important source of pathogenic microorganisms spreading into aquatic environments. However, there are few reviews discussing the presence and removal of pathogens in hospital wastewaters matrices. This review summarizes the pathogenic microorganisms including bacteria, fungi, viruses and parasites present in hospital wastewater, the related diseases and treatment processes. In addition, the removal of pathogens during hospital wastewater treatment process is reviewed, including the preliminary process, secondary process and tertiary process. Due to the growing concerns over the effects of the current global pandemic on hospital wastewater treatment process, further research is necessary to investigate the actual fate of pathogens in hospital wastewater and optimize disinfection processes.